Complete mitochondrial genome of the agarophyte red alga Gelidium vagum (Gelidiales). (August 2014) - Yang, Eun Chan; Kim, Kyeong Mi; Boo, Ga Hun; Lee, Jung-Hyun; Boo, Sung Min; Yoon, Hwan Su
Abstract We describe the first complete mitochondrial genome of Gelidium vagum (Gelidiales) (24, 901 bp, 30.4% GC content), an agar-producing red alga. The circular mitochondrial genome contains 43 genes, including 23 protein-coding, 18 tRNA and 2 rRNA genes. All the protein-coding genes have a typical ATG start codon. No introns were found. Two genes, secY and rps12, were overlapped by 41 bp.